STRATEGI PENGEMBANGAN USAHA SAPI POTONG DI PT BINTANG ADYA FARM - Listyowati, Esi Asyani; Budiyono, Haris; Bustomi, Muhammad Yazid; Gunawan, Rido (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2024)
Fattening beef cattle is one of the agribusiness ventures with quite promising long-term opportunities and attracts the interest of many actors to try it, thus triggering quite tight competition. One of the beef cattle fattening business actors is PT Bintang Adya Farm. This study aims to (1) Identify internal and external factors found in the beef cattle fattening business, (2) Compile alternative strategies for developing the beef cattle fattening business of PT Bintang Adya Farm, (3) Determine the priority of beef cattle fattening strategies at PT Bintang Adya Farm. The research method used is a descriptive method with SWOT analysis and QSPM analysis. The results of the study found five weaknesses and five strengths as well as four opportunities and threats at PT Bintang Adya Farm. The results of the interaction of internal and external factors in the SWOT matrix produced six business development strategies with strategic priorities, namely independent business development planning by cultivating young cattle